2013
DOI: 10.1080/10286020.2013.769966
|View full text |Cite
|
Sign up to set email alerts
|

A new sesquiterpene lactone fromSalvia plebeia

Abstract: A new eudesmanolide, 1α-acetoxy-8α,9β-dihydroxy-2-oxo-eudesman-3,7(11)-dien-8,12-olide (2), together with a known eudesmanolide, 1α-acetoxy-8α-hydroxy-2-oxo-eudesman-3,7(11)-dien-8,12-olide (1), and a known flavone, 4',5,7-trihydroxy-6-methoxyflavone (3), was isolated from the plant of Salvia plebeia. Three compounds were structurally elucidated by spectroscopic and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…A viny1 proton indicated that the second double bond was tetrasubstituted. These data are in accordance with those of previous studies on eudesmane-type sesquiterpenoids [16,17]. Thus, compound 2 was deduced to have a planar structure of 1-acetoxy-8-hydroxy-2-oxoeudesman-3,7(11)-dien-8,12-olide.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A viny1 proton indicated that the second double bond was tetrasubstituted. These data are in accordance with those of previous studies on eudesmane-type sesquiterpenoids [16,17]. Thus, compound 2 was deduced to have a planar structure of 1-acetoxy-8-hydroxy-2-oxoeudesman-3,7(11)-dien-8,12-olide.…”
Section: Resultssupporting
confidence: 91%
“…Jang et al investigated sesquiterpenoids and revealed that they inhibited IL-6-induced STAT3 activation [20]. Further studies are needed to isolate more sesquiterpenoids from SP as most of the reports have focused on flavonoids, diterpenoids, and triterpenoids [17].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological investigations have revealed that of the leaf extract of S. plebeia has anti-oxidative (27), anti-tyrosinase (28), anti-cancer (29) and hepatoprotective effects (26). The active components of S. plebeia comprise flavonoids (30,31), diterpenoids (32), lignin (33), aliphatic compounds (34) and sesquiterpenoids (35). Although S. plebeia leaves are used to prevent and treat skin aging-associated conditions, including inflammation, pigmentation and wrinkle formation, the exact underlying physicochemical and molecular mechanisms of its biological activity have remained elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Salvia plebeia R.Br., belonging to the Lamiaceae family, is prescribed as a folk remedy for treating cough, hepatitis, diarrhea, gonorrhea, and hemorrhages and is widely distributed across the globe, particularly in Korea, Japan, and China. S. plebeia has been reported to demonstrate pharmacological activities such as gastroprotective, anti-inflammatory, , antioxidant, , hepatoprotective, antiatherogenic, antiviral, and antiobesity effects and to contain phytochemical constituents such as sesquiterpenoids, diterpenoids, , lignans, , flavonoids, , phenolics, and aliphatic compounds …”
mentioning
confidence: 99%